Hak Kebebasan Berpendapat dan Berekspresi dalam Ruang Publik di Era Digital - Latipah Nasution (UIN Syarif Hidayatullah Jakarta, 2020)
AbstractDemocracy as an Indonesian government system has implications for equal rights, obligations and equal treatment for all its citizens. Freedom of opinion is basically a right owned by every individual guaranteed by the constitution, this is contained in Article 28E paragraph (3). The advancement of technology and information is one of the platforms in the delivery of opinions by the people in Indonesia. Communication technology with various kinds of social media has given freedom to each individual to express their opinions through various types of social media communication. The development of information technology media is characterized by various problems. The limitation of human rights in various aspects is a form of control over the avoidance of brutal and transgressing freedom.Keywords: Freedom of Opinion, Democracy, Communication Information Technology (ICT) AbstrakDemokrasi sebagai sistem pemerintahan Indonesia memberikan implikasi terhadap persamaan hak, kewajiban dan perlakuan yang sama bagi seluruh warga negaranya. Kebebasan berpendapat pada dasarnya merupakan hak yang dimiliki oleh setiap individu yang dijamin oleh konstitusi, hal ini termuat pada Pasal 28E ayat (3). Kemajuan teknologi dan informasi merupakan salah satu wadah dalam penyampaian pendapat oleh masyarakat di Indonesia. Teknologi komunikasi dengan berbagai macam media sosial telah memberikan kebebasan kepada tiap individu untuk mengekspresikan pendapatnya melalaui berbagai jenis media sosial komunikasi. Perkembangan media teknologi informasi diwarnai berbagai permasalahan. Pembatasan HAM dalam berbagai aspek merupakan bentuk kontrol terhindarnya kebebasan yang brutal dan melampaui batas.Kata kunci: Kebebasan Berpendapat, Demokrasi, Teknologi Informasi Komunikasi (TIK)